Cross-Sectional Imaging In Ocular And Orbital Lesions A Review - Apoorva Sehgal; Alpana Manchanda; Jyoti Kumar; Ruchi Goel; R K Saran; Ayush Jain (Delhi Journal of Ophthalmology)
Orbit is the site for a heterogeneous group of tumors and tumor-like conditions which often overlap in their clinical presentation and examination findings. Thus, a detailed imaging evaluation is warranted to reach a definitive diagnosis or narrow the list of differentials in challenging cases. Magnetic Resonance Imaging (MRI) with its exquisite soft tissue contrast resolution is the modality of choice with Computed Tomography and Ultrasound, reserved for specific indications. This review highlights the role of various imaging modalities in evaluating non-traumatic orbital lesions with a detailed account on imaging features of the commonly encountered lesions and their clinical relevance.